A VARIANT OF THE NASH EQUILIBRIUM THEOREM IN GENERALIZED CONVEX SPACES - Park, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
The existence theorem of pure-strategy Nash equilibrium due to H. Lu [Economics Letters 94 (2007) 459-462] is extended to generalized convex spaces. Consequently, our version can be applied to a broad class of abstract strategy spaces.